Optimization of CdS buffer layer for high‐performance Cu2ZnSnSe4 solar cells and the effects of light soaking: elimination of crossover and red kink. (16th January 2015) - Neuschitzer, Markus; Sanchez, Yudania; López‐Marino, Simon; Xie, Haibing; Fairbrother, Andrew; Placidi, Marcel; Haass, Stefan; Izquierdo‐Roca, Victor; Perez‐Rodriguez, Alejandro; Saucedo, Edgardo
Abstract: A spike‐like conduction band alignment of kesterite absorbers with a CdS buffer layer is one of the key factors for high‐performance solar cells using this buffer/absorber heterojunction combination. However, it can also be the origin of fill factor and current‐reducing distortions in current–voltage curves, such as light/dark curve crossover, or an s‐like curve shape for long wavelength monochromatic illumination (red kink) if light‐dependent defect states are present in the buffer layer. In this work, we show that by changing the cadmium precursor source from sulfate to nitrate salts for the chemical bath deposited cadmium sulfide for Cu2 ZnSnSnSe4 /CdS heterojunction solar cells red kink can be eliminated, and crossover greatly improved (and eliminated entirely after light soaking). These improvements lead to a decrease in series resistance and an increase in fill factor and increase power conversion efficiency from 7.0% to 8.2%. We attribute this improvement to a reduction of deep level acceptor‐like traps states inside the CdS layer, which are responsible for an increase of the conduction band spike up to a current blocking value for the sulfate precursor case. Furthermore, the effects of light soaking will be discussed. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Crossover of dark and illuminated current–voltage curves are commonly observed for kesterite‐based solar cells. The optimization of CdS buffer layer growth by chemical bath deposition using different cadmium salts results in the elimination of this crossover and improves the fill factor. The cause of the crossover and high series resistance could be identified as light‐sensitive compensating acceptor defects, most likely cadmium vacancies. Crossover can be drastically reduced by implementing a slow and controlled CdS growth process with cadmium nitrate, as opposed to the more commonly used cadmium sulfate.